1970
DOI: 10.1021/jf60171a028
|View full text |Cite
|
Sign up to set email alerts
|

Fate of benefin in soils, plants, artificial rumen fluid, and the ruminant animal

Abstract: Benefin, a selective, preemergence, soil-incorporated herbicide, decomposed rapidly in soil under defined anaerobic conditions, with approximately 5% detectable after 16 days; whereas, under defined aerobic conditions, 50% of the originally incorporated benefin was detectable after 120 days and only 12.1 % after 352 days. Identifiable degradation products were the dealkylated, reduced, and oxidized derivatives of benefin, and an unidentified polar mixture. Soil-incorporated 14C-labeled benefin was not readily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
1

Year Published

1975
1975
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 7 publications
1
17
1
Order By: Relevance
“…Much of the 14 C material was retained by the wax and cutin layers, but a small fraction apparently penetrated into the internal tissues (15). Benefin and trifluralin are not actively metabolized by plants, and unaltered herbicides are the major source of the radioactivity in plants, including tobacco, when treated with 14 C-benefin or -trifluralin (4,5,6,11). The objectives of this study were to determine some of the morphological and anatomical changes that occurred in tobacco as a result of exposure to vapors from benefintreated soil.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the 14 C material was retained by the wax and cutin layers, but a small fraction apparently penetrated into the internal tissues (15). Benefin and trifluralin are not actively metabolized by plants, and unaltered herbicides are the major source of the radioactivity in plants, including tobacco, when treated with 14 C-benefin or -trifluralin (4,5,6,11). The objectives of this study were to determine some of the morphological and anatomical changes that occurred in tobacco as a result of exposure to vapors from benefintreated soil.…”
Section: Introductionmentioning
confidence: 99%
“…Several processes including volatilization, photodecomposition, and microbial decomposition are involved in its dissipation. Golab et al (6) postulated that under anaerobic conditions, benefin is rapidly degraded by a sequence of reductive reactions, while under aerobic conditions, benefin is metabolized more slowly by oxidative dealkylation reactions. Both pathways result in the formation of polar products from aromatic amine precursors.…”
Section: Introductionmentioning
confidence: 99%
“…The herbicide benfluralin (N-butyl-N-ethyl-2,6-dinitro-4-trifluoromethy~ani~ine) has been introduced for the control of a wide variety of annual grasses and broadleaved weeds, a serious nuisance in many agronomic and horticultural crops. 1 Residue analyses have indicated that benfluralin, which is relatively persistent in the soil,2 does not become incorporated in the leaves, seeds or fruits of a wide variety of plants. Roots from plants grown in soil containing this herbicide are likely to contain a residue only in the region of contact with the treated soil.…”
Section: Introductionmentioning
confidence: 99%